Role of germinal centers for the induction of broadly-reactive memory B cells - Takahashi, Yoshimasa; Kelsoe, Garnett (Current opinion in immunology, 2017)
•Viral conserved domains are often concealed from the humoral responses.•Memory B cells counteract with viral mutations by germline-encoded cross-reactivity.•GC reactions fine-tune the specificity of memory B cells toward the conserved domains.•Permissive GC selection allows the fine-tuning of memory specificity.•Broadly-reactive B cells may be recruited into the memory pool with an attenuated T-cell help. Virus-specific memory B cells (Bmem) play a crucial role in protecting against variant viruses. The ability to recognize these variant viruses, defined as antibody breadth, is achieved in Bmem populations by two very different pathways, germline-encoded cross-reactivity and affinity-driven, somatic evolution in germinal centers (GCs) for conserved viral epitopes. The latter class of broadly-reactive Bmem cells are not cross-reactive per se, but bind epitopes crucial for viral fitness. Although these conserved epitopes are often weakly immunogenic, the GC reaction is surprisingly permissive for the continued survival/proliferation of B cells that bind with low affinity or react to cryptic epitopes, increasing their chance of memory recruitment. In this review, we discuss the adaptive strategies of B-cell memory to viral antigenic variations.